Unraveling the structural, electronic and magnetic properties of Mn1Pd n-1, Mn 2Pd n-2 and Pd n(n=13) clusters - Kaphle, G. C.; Adhikari, N. P. (Pragya Darshan प्रज्ञा दर्शन, 2023)
This work presents a systematic study of the geometric, electronic and magnetic properties of Pd clusters pristine and mono- and bi[1]doped with Mn: Pdn, Pdn−1Mn, Pdn−2Mn2 where n ≤13. We have used the density functional formalism with the spin polarized generalized gradient approximation. From the variety of possible structures with thirteen atoms, we found the icosahedral configuration to be the most stable as compared to the hexagonal, cub-octahedral and buckled bi-planar. The change in magnetic behavior of Pd clusters after doping with Mn has been observed. This communication is an attempt to understand that behaviour.